PERANCANGAN E-SCM PADA PT SUPERPOLY INDUSTRY - Rudy, Rudy; Jackson, Jackson; Desi, Christina; Hadi T, Ishak Eko (CommIT (Communication and Information Technology) Journal, 2009)
Manufacturing companies always strives to improve performance, namely in production of goods in time, management of material supply to prevent out of stock by exchanging information with suppliers, and on time delivery of goods to distributors to meet customer satisfaction on manufactured products. The purpose of this study is to analyse the supply chain management and to design the electronic supply chain management (e-SCM) on Superpoly Industry Company so it able to give accurate and reliable information also support the better supply chain acitivity for the company. The used research methods are preliminary steps (energize the organization, enterprise vision, supply chain value assessment, opportunity identification, and strategy decision) for the analysis and for the design consist of supply chain management strategic, customer and service management, manufacturing and supply chain planning, supplier relationship management, logistics resource management, and architecting. The conclusion is the e-SCM application will make it easier for the distributor to order merchandise from the company because information channel is open, which is website and information flow between supplier, company, and distribution is getting better.Keywords: supply chain management, electronic supply chain management, company